A concretização do conceito de desenvolvimento sustentável: uma análise jurisprudencial do conflito entre desenvolvimento econômico e o direito ao meio ambiente - Dias, Maria Rita Rebello Pinho (2010)
The main purpose of this study is to analyze the orientation adopted by the Brazilian courts in relation to the definition of sustainable development when it is deciding on the conflict between an economic activity and the environmental protection. This study s choice by jurisprudential analysis is justified by the observation that the sustainable environment is a very large and vague concept, which gives it a huge room for judicial intervention in the case. In view of this situation, it highlights the importance of studying judicial decisions on this matter, in order to verify whether there is any trend and uniform standard behavior by the magistrates. This study wants also to verify if the Courts ends adopted in its decisions not only legal criteria for defining sustainable development. This jurisprudential research expects to contribute with the identification of criteria used by the Brazilian Courts to settle disputes like those above mentioned, having a clearer view of how the concept of sustainable development has been implemented by this institution